PENGENDALIAN INTERNAL TERHADAP KREDIT CEPAT AMAN (KCA) PADA PT. PEGADAIAN CABANG MEGA MAS MANADO - Usman, Iin Febrianti; Elim, Inggriani; Lambey, Robert (GOING CONCERN : JURNAL RISET AKUNTANSI, 2017)
PT. Pegadaian are one of the formal institutions in Indonesia which under the law are allowed to do the financing by the form of quick credit distribution securely on the basis of legal pawn. The purpose to find out the internal control system against Secured Fast Credit (KCA) at PT. Pegadaian Branch Mega Mas Manado. The method used in this research is descriptive qualitative method. The data used in this study are primary data and secondary data, where the primary data obtained from the results of interview researchers with resource persons, as: interviews with finance staff and operational departments related to internal control. Data processing techniques used are interview techniques, observation, and documentation. Based on the results of research Scope of discussion on the internal control of fast credit secured at PT. Pegadaian Branch Mega Mas Manado includes a discussion related to the elements of internal control fast credit secured, namely a separate organizational structure of functional responsibilities, authority systems and record-keeping procedures that provide sufficient laws of wealth, debt, income and expenses, healthy practices in carrying out the duties and functions of each organizational unit and employees of a quality in accordance with their responsibilities.Keywords : Internal Control and PT. Pegadaian